Decoding debate in the Venetian Senate short stories of crisis and response on Albania (1392-1402) - Rojas Molina, Grabiela (Medicine in the medieval Mediterranean, 2022)
"Debate within the Venetian Senate at turn of the fifteenth century has long been opaque, as only an elite few were allowed access to Senate proceedings, their participation bound to secrecy. This volume offers a new interpretation of scribal intent, enabling hidden aspects of those discussions to come to light. By using documentation related to Venice's involvement in Albanian territories as a case study, this study unfolds the systematic yet secretive method by which scribes classified Senate discussions. The registers emerge as triumphs of precise and pragmatic codification within a milieu of information overflow."